Circularly Polarized Wideband Uniplanar Crossed-Dipole Antenna With Folded Striplines and Rectangular Stubs - Wang, Heesu; Byun, Gangil; Park, Yong Bae; Park, Ikmo (IEEE Access, 2023)
A circularly polarized (CP) wideband uniplanar crossed-dipole antenna is presented in this paper. The antenna constitutes a pair of identical crossed-dipole arms printed on the same plane of a dielectric substrate. Each crossed-dipole component is a pair of thin dipole arms that are perpendicular to each other and connected with a folded stripline for generating CP radiations. A pair of thin rectangular stubs are introduced on one dipole arm at the center of the antenna to improve impedance-matching bandwidth. Another set of rectangular stubs is attached at the sides of the dipole arms to broaden the axial ratio (AR) bandwidth. The antenna in free space is excited via a coaxial probe with a balun. It generates two adjacent AR bands that are merged into a wide AR bandwidth with bidirectional radiation patterns. Full-wave electromagnetic simulations are performed in the design process, and experiments are performed to validate the antenna design. The proposed antenna sized 42.4 mm ×42.4 mm ×0.2032 mm (0.57λ o × 0.57λ o× 0.0027λ o at 4.05 GHz) has an S11 < -10 dB impedance bandwidth of 2.92-5.15 GHz (55.26%) and a 3 dB AR bandwidth of 2.96-5.12 GHz (53.5%).
Keywords: Broad-band antenna; Circularly-polarized; Compact antenna; Crossed dipoles; Impedance; Rectangular stubs; Stripline; Uniplanar; Wide-band; circular polarization; Compact antenna; crossed dipole; uniplanar; wideband